Strategic Gap Analysis of Palestine Cybersecurity Performance in the Context of GCI, Kingdom of Saudi Arabia Cybersecurity Posture and Anti-Cybercrime Law, and Council of Europe Convention - Atrash, Amr; Farajallah, Mousa; Alsharif, Ibrahim; Shanti, Nedal (Palestine Polytechnic University (PPU), 2025)
Palestine rapid digital transformation is facing multiple challenges in the field of cybersecurity. An analysis of the Global Cybersecurity Index (GCI) for the years 2017–2024 revealed that Palestine's performance has declined compared to the leading vision of the Kingdom of Saudi Arabia [15][16][28]. This research aims to identify strategic gaps in the Palestinian legal and institutional framework for combating cybercrime (Decree 2018) using a mixed methodology that combines quantitative analysis of GCI data with qualitative comparative analysis of the Saudi Anti-Cybercrime Law (2007) and the standards of the Budapest Convention [6][11][12]. The research uses a parallel design to integrate the results of descriptive and trend data analysis with semi-structured interviews and comparative legal literature [29]. The analysis revealed significant gaps in the legal, regulatory, technical, developmental, and cooperation pillars with shortcomings in updating data protection legislation, reporting mechanisms, and international cooperation, and weak digital forensic investigation capabilities [28]. Accordingly, the research proposes a package of recommendations that includes updating legislation to protect privacy and data, establishing a national cybersecurity authority, enhancing technical and regulatory capabilities, and deepening international partnerships, with a phased timeline for measuring progress using indicators derived from the GCI.
Number of pages: 10, 2025 Engineering for Palestine Conference (ENG4PAL) PPU, Hebron, Palestine, September 29-30, 2025
Keywords: Strategic Gap Analysis, Palestine, Cybersecurity Performance, GCI, Kingdom of Saudi Arabia, Cybersecurity, Anti-Cybercrime Law, Council of Europe Convention